The integration of TPACK framework: practising collage by using Adobe Photoshop / Mohd Fadzil Mohd Arif - Mohd Arif, Mohd Fadzil (2014)
This study was conducted by using Technological Pedagogical Content Knowledge (TPACK) as a conceptual framework to assist the Visual Art Education (VAE) teachers in producing collage with Adobe Photoshop. In implementing technology for Visual Art Education, the use of Adobe Photoshop software was selected and integrated into the collage techniques. Collage is one of the techniques included in the Visual Art Education’ syllabus. The purpose of this study was to investigate the VAE teachers’ understanding and their implementation of TPACK framework in their teaching. Thus, the teaching and learning of collage techniques will be conducted with the integration of technology, pedagogy, content and knowledge. The finding of this study to identify the knowledge of the VAE teachers in producing the collage artwork by using Adobe Photoshop.